PENGARUH CUSTOMER SATISFACTION DAN CORPORATE IMAGE TERHADAP CUSTOMER LOYALTY PROVIDER â€œXLâ€ DI SURABAYA - HENDRAWAN, BRIAN (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2013)
The company's goal to provide the satisfaction of customers as well as the existence of a positive assessment of the customers against the company will make the customers remain loyal customers. Maintain a customer is far more difficult than finding new customers. Company's image a little number effect on customer loyalty with services or products of an enterprise. The research aims to know the influence of customer satisfaction, toward corporate image, and customer loyalty XL in Surabaya. In this study used is the conclusive research on the study of experimental or causal research. Sampling-taking techniques used are non probability sampling. The type of method used is the purposive sampling. The sample used was 200 consumer XL in Surabaya. Data were collected using a questionnaire. The technique used is the analysis of structural equation modeling with Lisrel program assistance. The results of this analysis indicate that customer satisfaction affect corporate image, and customer loyalty. The research also found that corporate image can affect customer loyalty.